The Public Face of Scholarship - Larry E. Ribstein (Washington University Law Review, 2006)
This essay focuses on the relationship between academic weblogs, or blogs, and journalism. I see academic blogs as a form of what I called in a separate paper “amateur journalism.” This comment focuses on the type of writing that is both most distinctive to scholars and connects most closely with professional journalism—that is, scholars’ use of blogs to engage with the public. Part I reviews the distinction between amateur and professional journalism and describes types of academic blogs. Part II focuses on “publicly engaged academic posts,” or PEAPs, and discusses the changes these blogs may bring to professional journalism.
Keywords: Journalism; Blogs; Law – Study & amp; teaching; Amateur journalism; Legal literature; United States